Evaluation of the effect of two substrates on the development of Moringa oleifera Lam (Fam: Moringaceae) (moringa) under nursery conditions - Ontivero, Y.; García, Diandra; Loiret, F. G. (Cuban Journal of Agricultural Science, 2021)
To compare the effect of adding sawdust to substrate on the growth of M. oleifera under nursery conditions, soil (red ferralitic soil) and soil:sawdust were used as substrates, with differences in field capacity (soil: greater sawdust). Growth indexes and parameters were measured, as well as concentrations of photosynthetic pigments. The moringa cultivated in soil showed greater growth in height (24.0 cm), accumulation of dry biomass in the stem (0.22 g) and concentration of photosynthetic pigments compared to those cultivated in soil: sawdust (height: 19.8 cm and dry biomass: 0.18 g). While soil:sawdust stimulated leaf length at 14 days and root system at 28 days, as well as absolute (0.02 g day-1) and relative (0.04 mg mg-1 day-1) growth rate. With this experiment, it is concluded that the establishment of moringa under nursery conditions, with soil as substrate, stimulates the production of photosynthetic pigments, growth in height, and dry biomass of the stem. Soil:sawdust substrate increases leaf dimensions, root biomass, and absolute and relative growth rate, as well as providing a more equitable growth between root system and the aerial part of plants. Sowing in soil:sawdust is a viable alternative for places in which rains are infrequent. Keywords: growth analysis, sawdust, field capacity, photosynthetic pigments, plantlet